Morphometric study of gastric mucosa in dogs submitted to proximal gastric vagotomy, splenectomy or proximal gastric vagotomy associated with splenectomy - Martinez,Carlos Augusto Real (2002)
OBJECTIVE: The aim of the present study was to evaluate the effects of total splenectomy and proximal gastric vagotomy (PGV) isolated or associated to the vascularization of the stomach. METHODS: Twenty-eight dogs were distributed in: group A - animals undergoing laparotomy and gastric manipulation; group B - animals undergoing PGV; group C - animals undergoing PGV and splenectomy; and group D - animals undergoing splenectomy alone. All animals were sacrificed on the 7th postoperative day, and immediately followed by infusion of xanthene dye into the thoracic aorta. On the gastric mucous surface, the formation of stained areas and other areas lacking staining was measured by millimeter squares, planimetry and the computerized morphometry method. RESULTS: The formation of an area lacking in staining along the lesser gastric curvature was seen in all animals of groups B and C, which was significantly increased in group C, although in groups A and D such areas were not observed. CONCLUSION: These results showed that, in animals with splenectomy, the vascularization of the stomach was capable of perfusing the whole organ surface, but in animals with PGV alone or associated with splenectomy there was a notable decrease in blood supply throughout the area of the lesser gastric curvature, which suggests the ischemic impairment of this region.